PERJUANGAN RAKYAT KUALA TUNGKAL JAMBI DALAM MENGHADAPI AGRESI MILITER BELANDA TAHUN 1945-1949 - Daniel Arnop Hutapea; Marwoto Saiman; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:Indonesian Independence on August 17, 1945 on the occupation ofJapan, the Netherlands is considered as an opportunity to rebuild their colonies inIndonesia. Various diplomatic efforts in the form of treaties and agreements that theDutch did not succeed in making Indonesia back is subject to Dutch rule. As for theDutch finally forced to take steps to regain control of Indonesia with its military power.Dutch desire to regain control of Indonesia realized with military aggression in variousparts of Indonesia. This gives rise to the struggle of the people in all regions ofIndonesia in an effort to face the onslaught of Dutch military aggression. As in this casethe people's struggle in the face of the Dutch military aggression also occur in KualaTungkal in Jambi. This study aims to determine (1) Condition Kuala Tungkal Jambibefore the Dutch military aggression. (2) The organizational forms of struggle. (3) theprocess of the struggle of the people of Kuala Tungkal in Jambi in the face of the Dutchmilitary aggression. (4) Completion and final outcome of the struggle of the people ofKuala Tungkal in Jambi in the face of the Dutch military aggression. The method usedin this study was a qualitative research approach history (History) and data collectiontechniques in the form of literature, observation, documentation and interview. Theresults showed that during the Dutch military aggression in Indonesia, the presence ofthe people's struggle in the face of the Dutch military aggression that occurred in KualaTungkal in Jambi in the fight against the Dutch to defend the people's power in theregion Kuala Tungkal Indonesia Jambi.Keywords: Military Aggression, The Kuala Tungkal Jambi People’s